HIV sexual risk behavior and preferred HIV prevention service outlet by men who have sex with men in Nigeria. - Emmanuel, Godwin; Folayan, Morenike Oluwatoyin; Ochonye, Bartholomew; Umoh, Paul; Wasiu, Bashiru; Nkom, Mercy; Iorwa, Apera; Anenih, James (BMC Health Services Research, 2023)
10p